Influence of soil conservation techniques on growth and yield of maize (Zea mays L.) in Terai region of West Bengal - De, B; Bandyopadhyay, S (SAARC Journal of Agriculture, 2014)
The climate of the terai region of West Bengal, India in general, is subtropical par humid to tropical with light textured acid soil with the problems like low moisture retention, low water use efficiency, leaching of bases, soil erosion, limited availability of multiple plant nutrients and restricted activity of beneficial soil micro-organisms. To combat these soil health related problems and to improve the overall productivity of North Bengal, a comparison between the conventional and conservation tillage was taken up and the immediate results were measured in terms of growth, yield attributes and yield. In the first two years of experimentation, though different growth attributes, grain yield, stover yield, and different yield attributing characters such as kernel rows cob-1, number of kernels row-1, 100 seed weight (g), number of seeds cob-1, girth of cob, length of cob and number of effective cob plant-1 were higher in conventional tillage as compared to conservation tillage but in terms of soil heath characteristics, conservation tillage had a meaningful remark from the initial years towards the future food security. Mulching @ 4 t ha-1 was found to have performed better than unmulched treatments. Application of 75% recommended dose of fertilizer + Vermicompost @ 10 t ha-1 resulted in better growth and yield attributes which directly influenced to have higher grain and stover yield. DOI: http://dx.doi.org/10.3329/sja.v11i1.18390 SAARC J. Agri., 11(1): 133-147 (2013)